Effect of Punica granatum on the virulence factors of cariogenic bacteria Streptococcus mutans. (September 2016) - Gulube, Zandiswa; Patel, Mrudula
Abstract: Dental caries is caused by acids produced by biofilm-forming Streptococcus mutans from fermentable carbohydrates and bacterial byproducts. Control of these bacteria is important in the prevention of dental caries. This study investigated the effect of the fruit peel of Punica granatum on biofilm formation, acid and extracellular polysaccharides production (EPS) by S. mutans. Pomegranate fruit peels crude extracts were prepared. The Minimum bactericidal concentrations (MBC) were determined against S. mutans . At 3 sub-bactericidal concentrations, the effect on the acid production, biofilm formation and EPS production was determined. The results were analysed using Kruskal-Wallis and Wilcoxon Rank Sum Tests. The lowest MBC was 6.25 mg/mL. Punica granatum significantly inhibited acid production (p < 0.01). After 6 and 24 h, it significantly reduced biofilm-formation by 91% and 65% respectively (p < 0.01). The plant extract did not inhibit the production of soluble EPS in either the biofilm or the planktonic growth. However, it significantly reduced the insoluble EPS in the biofilm and the plantktonic (p = < 0.01) form of S. mutans. The crude extract of P. granatum killed cariogenic S. mutans at high concentrations. At sub-bactericidal concentrations, it reduced biofilm formation, acid and EPS production. This suggests that P. granatum extract has the potential to prevent dental caries. Graphical abstract: Highlights: At high concentrations, pomegranate fruit peel kills cariogenic Streptococcus mutans . At subinhibitory concentrations it reduces bacteria biofilm formation. At subinhibitory concentrations it also reduces acid and EPS production. Therefore Punica granatum extract has the potential to prevent dental caries.